Urinary neutrophil gelatinase-associated lipocalin (NGAL) can potentially predict vascular complications and reliably risk stratify patients with peripheral arterial disease - Mehroz Ehsan; Muzammil H. Syed; Abdelrahman Zamzam; Niousha Jahanpour; Krishna K. Singh; Rawand Abdin; Mohammad Qadura (Scientific Reports, 2022)
Abstract Neutrophil gelatinase-associated lipocalin (NGAL) is expressed in atherosclerotic plaques and implicated in the development of cardiovascular diseases. Peripheral arterial disease (PAD) is an atherosclerotic disease that often results in major cardiovascular events. This study aimed to prospectively examine the potential of urine NGAL (uNGAL) in predicting worsening PAD status and major adverse limb events (MALE). Baseline urine NGAL (uNGAL) and urine creatinine (uCr) concentrations were measured in PAD (n = 121) and non-PAD (n = 77) patients. Levels of uNGAL were normalized for urine creatinine (uNGAL/uCr). Outcomes included worsening PAD status, which was defined as a drop in ankle brachial index (ABI) > 0.15, and major adverse limb events (MALE), which was defined as a need for surgical revascularization or amputations. PAD patients had 2.30-fold higher levels of uNGAL/uCr [median (IQR) 31.8 (17.0–62.5) μg/g] in comparison to non-PAD patients [median (IQR) 73.3 (37.5–154.7) μg/g] (P = 0.011). Multivariate cox analysis showed that uNGAL/uCr levels were independently associated with predicting worsening PAD status and MALE outcomes. Cumulative survival analysis, over follow up period, demonstrated a direct correlation between elevated uNGAL/uCr levels and PAD disease progression and MALE outcomes. These data demonstrate an association between elevated uNGAL/uCr levels and worsening PAD disease status and MALE outcomes, indicating its potential for risk-stratification of PAD patients.